Perancangan Jok Ergonomis Dalam Fabrikasi Mobil Minimalis Roda Tiga - M. Faiz Fazlur Rahman; Anda Iviana Juniani; Tri Andi Setiawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
This study aims to create ergonomic seat design, which will be applied to the minimalisttricycle car. Seats that will be designed in this study has two designs, the front seat for one driver andthe back seat for two passengers. In ergonomic seat design is used Ulric method for the process ofmaking a product design. The design of the seat should refer to the anthropometry of the Indonesianhuman body in order to create an ergonomic seat, because this product is intended for the Indonesianpeople. Some of the design concepts that have been created will be selected one the best designamong several design concepts. The selection of design concepts refers to three things. First, basedon ergonomic values that can be analyzed using RULA (Rappid Upper Limb Assessment) method thatcontain in softwere catia. Second, based on the aesthetic value that gained from the distribution ofaesthetic questionnaire of products. Third, based on the level of convenience that determined by theseat upholstery materials used. The results of this study indicate that the three front and back seatsdesign can be categorized to be ergonomic. That statement is based on the result of RULA valueanalysis which shows the final value 2, which is in the table described that the risk of injury withvalue 2 is can be included into the acceptable category and has no risk of injury. Based on the therereferences that have been described, and from the three concepts that have been made for the frontseat and back seat, was chosen concept 2 for the front seat because in the process of design conceptselection obtained absolute value 4 and the relative value 34.12%. In the back seat was chosenconcept 2 because in the process of design concept selection obtained absolute value 4.03 andrelative value 34.7